2017
DOI: 10.1037/dev0000271
|View full text |Cite
|
Sign up to set email alerts
|

Classroom displays—Attraction or distraction? Evidence of impact on attention and learning from children with and without autism.

Abstract: (2017) 'Classroom displays -attraction or distraction? Evidence of impact on attention and learning from children with and without autism.', Developmental psychology., 53 (7). pp. 1265-1275. Further information on publisher's website:Publisher's copyright statement:c 2016 APA, all rights reserved. This article may not exactly replicate the nal version published in the APA journal. It is not the copy of record.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 38 publications
13
56
0
Order By: Relevance
“…The findings are reflected in research regarding the negative impact of cluttered homes on subjective wellbeing (Roster et al 2016), decreased performance and increased stress as a result of the attentional effects of clutter (McMains and Kastner 2011), and a link between clutter and high levels of the stress hormone, cortisol (Arnold et al 2012). These findings also align with research indicating that cluttered homes and classrooms may be detrimental to attention, cognition, and learning (Fisher et al 2014;Hanley et al 2017;Tomalski et al 2017).…”
Section: Discussionsupporting
confidence: 55%
“…The findings are reflected in research regarding the negative impact of cluttered homes on subjective wellbeing (Roster et al 2016), decreased performance and increased stress as a result of the attentional effects of clutter (McMains and Kastner 2011), and a link between clutter and high levels of the stress hormone, cortisol (Arnold et al 2012). These findings also align with research indicating that cluttered homes and classrooms may be detrimental to attention, cognition, and learning (Fisher et al 2014;Hanley et al 2017;Tomalski et al 2017).…”
Section: Discussionsupporting
confidence: 55%
“…Executive function has been identified as a significant factor in school participation for autistic pupils (Zingerevich and LaVesser, 2009); 85% of autistic pupils experienced difficulties in the classroom with planning (Fernández‐Andrés et al, 2015) and 37% of autistic pupils were found to have difficulty maintaining attention on classroom tasks (Ashburner et al, 2010). Autistic pupils were found to give less attention to teachers giving instruction (Higuchi, Ishizaki, Noritake et al, 2017), and were more affected by distraction (Hanley, Khairat, Taylor et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The participants are overwhelmingly male with a total of 1455 boys and only 192 girls included in the selected studies; in the studies with both male and female autistic pupils, the average ratio was 7.5 males to every female participant. A further two studies contained only male participants (Hannah and Topping, 2012; Rodríguez‐Medina, Rodríguez‐Navarro, Arias, Arias and Anguera, 2018) and six studies did not report the gender of the participants (Hanley et al, 2017; McKenney, Stachniak, Albright, Jewell and Dorencz, 2016; Reed, Osborne and Waddington, 2012; Symes and Humphrey, 2010, 2012; Wainscot et al, 2008). Some smaller studies had more balanced ratios, for example Locke et al (2010) with four boys and three girls, but the small overall numbers do little to balance the overall gender ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention is the key to successful learning (Hanley et al, 2017). In line with the advancements in technologies and the proliferation of digital devices, learning has undergone a lot of changes.…”
Section: Introductionmentioning
confidence: 99%